Identification and characterization of fungal pathogen causing charcoal rot disease of Ananas comosus in Johor and Negeri Sembilan - Maarof, Nur Shazmine (2016)
Ananas comosus or commonly known as pineapple is from the family Bromeliaceae. It is a commercial fruit cultivated in dry, well-drained tropical habitats. In Malaysia, Johor and Negeri Sembilan states are the major producers of pineapple. Charcoal rot disease is one of the most significant diseases of pineapple in Malaysia causing decrease in yield and quality of the fruit. In order to take preventive and curative measures against charcoal rot of pineapple, the identity of the causal pathogen is essential. Thus, this study was conducted with objectives of i) To isolate the causal fungal pathogen from the symptomatic Ananas comosus tissues and ii) To identify the isolated fungal pathogen via morphological and molecular characteristics. The fungi were isolated from symptomatic Ananas comosus tissues and characterized morphologically based on cultural and microscopic characteristics. 11 isolates that met the criteria of the black (charcoal rot) fungi were chosen from 46 total isolates of the total samples for further molecular identification that was carried out by extracting genomic DNA using QIAGEN DNeasy Plant Mini Kit and amplification of internal transcribed spacer (ITS) region of the DNA via ITS1 and ITS4 primer sets and finally sequenced. Later, sequences obtained were analysed using BLAST application on GenBank sequence database to achieve species identity. Finally, pathogenicity test was carried out on susceptible pineapple seedlings to reproduce similar symptoms of charcoal rot and further confirm the causal pathogen. In this study, Lasiodiplodia theobromae and Neoscytalidium dimidiatum were identified as the causal pathogen of charcoal rot disease in Ananas comosus because they produce the same symptoms produced by the previous isolated diseased plants.